PEMBANGUNAN GEDUNG SEKOLAH DAN RUANG KELAS BARU DI KABUPATEN SELUMA PASCA PEMEKARAN - Hambali Hambali Hambali (UNIVERSITAS BENGKULU, 2016)
This article was written to describe the construction of school buildings and classrooms in Seluma post- expansion . Research using qualitative descriptive methods . The data collection isdone by observation , interviews and documention research. The results showed that the construction of school buildings and classrooms in the post- expansion Seluma done based onanalysis of community needs . Development using funds provided by local governments and the central government in the form of a special allocation fund (DAK). There are 41 new school construction and more construction of new classrooms in Seluma since 2004. The central government and local governments continue to conduct evaluations and supervition to ensure that the process of construction of school buildings and classrooms run effectively and efficiently .Keywords : building schools and new classrooms , expansion area , Seluma